Assédio Aproximações Sociojurídicas à Sexualidade - Oliveira, Ana (Contemporânea, 2022)
Harassment is a category that has been gaining ground in contemporary normative debate, appearing in political-governmental agendas, in the repertoire of social activism and in academic-scientific production. Both the movement and the feminist-inspired argumentation have constituted one of the great drivers of its public projection, helping to frame harassment in a cosmovision and in an economy of meaning with special regulatory implications in the labor and criminal spheres. In this book, the author views harassment as a device for observing the limits, potentialities and epistemological contradictions that cross the field, seeking to expose the consensus and cultural conflicts that the legal function (labor and criminal), the presumption about the subject (male or female) and the status of sexuality pose to feminist theories and social studies of law. It also seeks to demonstrate to what extent and in what terms the increasing legal density of harassment, driven or supported by different critical and feminist sources, instead of witnessing a progressive, cumulative and expansive logic of anti-patriarchal aspiration, puts the vices in evidence above all. and the political-epistemological paradoxes that permeate the way in which the field of sexuality is thought, prescribed and protected, forcing a critical return to the subject, structure and law as unfinished objects and constituents of social life.